2010
DOI: 10.1111/j.1365-3156.2010.02513.x
|View full text |Cite
|
Sign up to set email alerts
|

Situational analysis of varying models of adherence support and loss to follow up rates; findings from 27 treatment facilities in eight resource limited countries

Abstract: Summaryobjectives Large-scale provision of ART in the absence of viral load monitoring, resistance testing, and limited second-line treatment options places adherence support as a vital therapeutic intervention. We aimed to compare patient loss to follow up rates with the degree of adherence support through a retrospective review of patients enrolled in the AIDSRelief program between August 2004 and June 2005.methods Loss to follow up data were analysed and programs were categorised into one of four tiered lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Family Size: The positively significant relationships among household size and wasting, and underweight could be explained by the fact that the family meal is distributed among large numbers of household members resulting to inadequate diet for an extended period eventually causing malnutrition which is similar with the findings of other study conducted in Tanzania or Kenya [16].…”
Section: The Results Of Multivariate Probity Regressionsupporting
confidence: 81%
“…Family Size: The positively significant relationships among household size and wasting, and underweight could be explained by the fact that the family meal is distributed among large numbers of household members resulting to inadequate diet for an extended period eventually causing malnutrition which is similar with the findings of other study conducted in Tanzania or Kenya [16].…”
Section: The Results Of Multivariate Probity Regressionsupporting
confidence: 81%
“…The seventh type of community support strategy is Directly Observed Therapy (DOT) for ART , employing a community member close to the patient to directly monitor the daily medication intake – a strategy modelled after an effective method for controlling tuberculosis [47,67]. The eighth group of community support providers, labelled adherence supporters , are trained to promote healthy behaviours, provide HIV/AIDS&ART-related knowledge and skills and promote adherence by providing psychosocial support [20,21,46,49,56,57]. The final form of community support is labelled home-based care volunteers .…”
Section: Resultsmentioning
confidence: 99%
“…In Uganda, it was found that 1.2% of patients discontinued ART because of a belief in spiritual healing [57]. Programs with home- and community-based services had a lower loss to follow-up rate (1-5%) compared to programs without these services (10-14%) [58-63]. …”
Section: Discussionmentioning
confidence: 99%